Building Blood Vessels—One Rho GTPase at a Time - Haley Rose Barlow; Ondine Cleaver (Cells, 2019)
Blood vessels are required for the survival of any organism larger than the oxygen diffusion limit. Blood vessel formation is a tightly regulated event and vessel growth or changes in permeability are linked to a number of diseases. Elucidating the cell biology of endothelial cells (ECs), which are the building blocks of blood vessels, is thus critical to our understanding of vascular biology and to the development of vascular-targeted disease treatments. Small GTPases of the Rho GTPase family are known to regulate several processes critical for EC growth and maintenance. In fact, many of the 21 Rho GTPases in mammals are known to regulate EC junctional remodeling, cell shape changes, and other processes. Rho GTPases are thus an attractive target for disease treatments, as they often have unique functions in specific vascular cell types. In fact, some Rho GTPases are even expressed with relative specificity in diseased vessels. Interestingly, many Rho GTPases are understudied in ECs, despite their known expression in either developing or mature vessels, suggesting an even greater wealth of knowledge yet to be gleaned from these complex signaling pathways. This review aims to provide an overview of Rho GTPase signaling contributions to EC vasculogenesis, angiogenesis, and mature vessel barrier function. A particular emphasis is placed on so-called “alternative” Rho GTPases, as they are largely understudied despite their likely important contributions to EC biology.